Legal Aspects of Political Party Internal Conflict Resolution: A Case Study in Indonesia - Hartati, Hartati; Zarkasi, Zarkasi; Syamsir, Syamsir; Putra, Firmansyah; Subekti, Dimas; Amin Ayub, Zainal (Al-Risalah, 2025)
This research aims to explain the dispute resolution mechanism of political parties in Indonesia. This research uses normative juridical methods. The findings of this study are based on the provisions in Article 32, paragraph (2), which, on the one hand, position the Party Court as the first-level court in resolving internal political party disputes. Still, the decision of the Party Court as a first-level decision is not final. Then, the position of the party court also does not stand independently, but is still bound internally by the organization. Thus, it is vulnerable to interest intervention in every decision. Furthermore, based on the regulations of the Political Party Law regarding the settlement of party disputes, it has not applied the principles of simple, fast, and low-cost justice. Therefore, regulating political party dispute resolution institutions in Indonesia should be redesigned to have a single-entry point, namely, through a special court. In addition, changing the position of the political party dispute resolution institution as a special judicial body under the general court will make decisions in the field of political party disputes binding for all parties. This research contributes to the development of institutional theory and judicial law in the context of the political system. On the other hand, this research also directly relates to constitutional practice and legal reform in Indonesia, particularly in the context of reforming regulations for resolving disputes within political parties.